The dose regimen formulation of doxycycline hydrochloride and florfenicol injection based on ex vivo pharmacokinetic-pharmacodynamic modeling against the Actinobacillus pleuropneumoniae in pigs - Yuanyuan Yuan; Boyu An; Shuyu Xie; Wei Qu; Haihong Hao; Lingli Huang; Wanhe Luo; Jixiang Liang; Dapeng Peng (BMC, 2023)
Abstract Doxycycline hydrochloride and florfenicol combination (DoxHcl&FF) is an effective treatment for respiratory diseases. In the study, our objective was to evaluate the activity of DoxHcl&FF against Actinobacillus pleuropneumoniae (APP) in porcine pulmonary epithelial lining fluid (PELF) and the optimal dosage scheme to avoid the development of resistance. The DoxHcl&FF was administered intramuscularly (IM) at 20 mg/kg, and the PELF was collected at different time points. The minimum inhibitory concentration (MIC) and time-mortality curves were also included in the study. Based on the sigmoid Emax equation and dose equations, the study integrated the in vivo pharmacokinetic data of infected pigs and ex vivo pharmacodynamic data to obtain the area under concentration time curve (AUC0-24h)/MIC values in PELF and achieve bacteriostatic activity, bactericidal activity and the virtual eradication of bacteria. The study showed that the combination of DoxHcl and FF caused no significant changes in PK parameters. The peak concentration (Cmax) of FF in healthy and diseased pigs was 8.87 ± 0.08 μg/mL and 8.67 ± 0.07 μg/mL, the AUC0-24h were 172.75 ± 2.52 h·μg/mL and 180.22 ± 3.13 h·μg/mL, the Cmax of DoxHcl was 7.91 ± 0.09 μg/mL and 7.99 ± 0.05 μg/mL, and the AUC0-24h was 129.96 ± 3.70 h·μg/mL and 169.82 ± 4.38 h·μg/mL. DoxHcl&FF showed strong concentration-dependent tendencies. The bacteriostatic, bactericidal, and elimination activity were calculated as 5.61, 18.83 and 32.68 h, and the doses were 1.37 (bacteriostatic), 4.59 (bactericidal) and 7.99 (elimination) mg/kg. These findings indicated that the calculated recommended dose could assist in achieving more precise administration, increasing the effectiveness of DoxHcl&FF treatment for APP infections.